Vitamin D Deficiency and Outcomes After Ankle Fusion: A Short Report. (May 2022) - Ramanathan, Deepak; Emara, Ahmed K.; Pinney, Stephen; Bell, Andrea; Miniaci-Coxhead, Sara Lyn
Background: Vitamin D deficiency has been postulated as a cause for impaired bone healing and remodeling. The purpose of this study was to assess the potential association between low vitamin D levels and reoperation for nonunion following ankle fusion surgery. Methods: All adult patients (aged ≥18 years) who underwent ankle fusion procedures at a tertiary referral center from January 2010 to January 2019 with available vitamin D levels within 12 months preoperatively were retrospectively reviewed (n = 47). Patients were categorized as vitamin D deficient (<30 ng/mL) vs normal (31-80 ng/mL). The primary outcome was the incidence of reoperation secondary to nonunion. Secondary outcomes included incidence of reoperation not related to nonunion and the need for repeat reoperation. Results: The average level in the vitamin D–deficient group (n = 17; 36.2%) was 16.9 vs 46.4 ng/mL in the normal group (n = 30; 63.8%). All recorded reoperations for nonunion occurred exclusively in the vitamin D–deficient cohort (4/17 [23.5%]; P = .013). There were similar reoperation rates for causes other than nonunion (2/17 [11.8%] vs 4/30 [13.3%]; P > .99) and repeat reoperation rates (3/17 [17.6%] vs 1/30 [3.3%]; P = .128) among vitamin D–deficient vs normal patients. Conclusion: Vitamin D deficiency may be associated with an increased risk of reoperation for nonunion after ankle fusion.